Factors influencing conversion of laparoscopic cholecystectomy into open cholecystectomy - Tripathi, Ankur Dutt; Qazi, Imran; Tripathi, Shashank Shekhar (International Surgery Journal, 2019)
Background: Laparoscopic cholecystectomy may be rendered difficult by various problems encountered during surgery, such as difficulty in accessing the peritoneal cavity, creating a pneumoperitonium, dissecting the gall bladder, pericholecystic adhesions and adhesions between the common bile duct the cystic duct and the cystic artery (calot’s triangle) or extracting the excised gall bladder, injury to common bile duct, bowel and iliac vessels. These conditions may lead surgeons to perform conventional open cholecystectomy. Methods: The general biodata was collected. A detailed history was taken with special reference to duration of right upper quadrant pain or epigastric pain, its periodicity, its aggravation by fatty meals and relief by oral or parental analgesics. Fever, jaundice or any previous attacks of cholecystitis. A relevant general physical examination and systemic examination was done and findings recorded, routine laboratory investigation was done. All cases were then subjected to ultrasound examination with 2-5MHz curvilinear array transducer with an aim to assess. Results: The univariate analysis sex proved to be significantly predictive of conversion in the present study. Execution of ERCP before the intervention proved associated with an increased risk for conversion in our study. Stone position as significant factor for conversion while stone size was not significant. No significant association between fever and conversion our study. Conclusions: Male gender, GB wall thickness, stone position, stone size, ultrasound signs of pericholecystitis, acute cholecystitis, were significantly associated with conversion.